Intravitreal bevacizumab (Avastin®) for diabetic retinopathy at 24-months: The 2008 Juan Verdaguer-planas lecture (2010)
Diabetic retinopathy (DR) remains the major threat to sight in the working age population. Diabetic macular edema (DME) is a manifestation of DR that produces loss of central vision. Proliferative diabetic retinopathy (PDR) is a major cause of visual loss in diabetic patients. In PDR, the growth of new vessels is thought to occur as a result of vascular endothelial growth factor (VEGF) release into the vitreous cavity as a response to ischemia. Furthermore, VEGF increases vessel permeability leading to deposition of proteins in the interstitium that facilitate the process of angiogenesis and macular edema. This review demonstrates multiple benefits of intravitreal bevacizumab (IVB) on DR including DME and PDR at 24 months of follow up. The results indicate that IVB injections may have a beneficial effect on macular thickness and visual acuity (VA) in diffuse diabetic macular edema. Therefore, in the future this new therapy could replace or complement focal/grid laser photocoagulation in DME. In PDR, this new option could be an adjuvant agent to pan-retina photocoagulation so that more selective therapy may be applied. In addition, we report a series of patients in which tractional retinal detachment developed or progressed after adjuvant preoperative IVB in severe PDR. © 2010 Bentham Science Publishers Ltd.